Creating warm dense matter and studying structural properties - Hartley, N (2015)
Warm dense matter is an area of the phase diagram between solids and classical plasmas, but poorly described by theoretical descriptions of both. Collective oscillations and quantum effects all play significant roles in its structural behaviour and equations of state. Aside from its complexity, work on this state is significant as a stepping stone towards achieving energetically viable nuclear fusion, as well as representing a laboratory analogue for planetary cores and other astrophysical phenomena. X-ray scattering, using beams from X-ray free electron lasers, is used to probe the structure of samples in this state, and is shown to compare well to theoretical descriptions. Angle-resolved scattering showed sharper than expected peaks, suggesting stronger interparticle correlation than expected. Using the beam in self-seeded mode, scattering from ion acoustic waves in warm dense matter was observed for the first time, confirming theoretical descriptions of the phenomena but raising further questions due to an elastic peak in the spectra. Similar experiments in the future will allow models of ionic behaviour to be tested directly, and potentially determine the source of this feature. X-ray diffraction was used to study the evolution of samples heated by proton, electron or photon irradiation, with the aim of resolving the temperature evolution of the species within the sample. The results suggest that, although the behaviour in metallic samples is well described by lowtemperature approximations, that of graphite is more complex and does not agree with the models available.